An algebraic structure for Moufang quadrangles - Medts, Tom de, 1980- (Memoirs of the American Mathematical Society, 2005)
Introduction Definition Some identities From quadrangular systems to Moufang quadrangles From Moufang quadrangles to quadrangular systems Some remarks Examples The classification Appendix A. Abelian quadrangular systems Bibliography.